Too many puppies - Brewster, Patience (New York : Scholastic, 1997)
A little girl looks forward to keeping all of my Milly's puppies, but when they begin to make big demands on her, she changes her mind about them.
Keywords: Dogs -- Fiction; Animals -- Infancy -- Fiction